Análise da dinâmica vertical de um protótipo baja SAE para dimensionamento da suspensão - Zucolotto, João Victor (Universidade Federal de São Carlos, 2020)
The present work lists and explains the main considerations for the suspension design of a mini Baja off-road prototype, based on the modeling and multibody analysis of its vertical dynamics. The work includes both the front and rear suspension, in which parameters of stiffness and damping and their respective influences on the behavior of the suspension and the vehicle are analyzed. It is an iterative process of simulations with the objective of establishing ideal values of parameters in order to obtain a dynamic behavior close to the expected one within the limitations imposed on this type of vehicle, such as the competition regulations for example. An improvement in vehicle performance is expected, and, for this type of vehicle, this boils down to high capacity to overcome obstacles combined with minimizing of the efforts transmitted to other car subsystems, including the driver. Several conditions which are found in the competition environment and considered to be among the most critical ones are simulated. The terrain type the car is subjected to, the types of tests and obstacles in competitions, as well as the characteristics of tires, shock absorbers and springs are the parameters of the greatest importance. The UFSCar Baja Team does not have a properly documented suspension project that will serve as a basis for future performance studies and improvements. The objective of this work is the adequate development of the vertical dynamics project of the suspension of the UFSCar Baja, using design methodologies such as: analysis of dynamic systems, design documentation and computer simulations. As a result, it is expected to obtain a suspension proposal that satisfies the demands of the UFSCar Baja project.
Analysis of the vertical dynamics of a baja SAE prototype for dimensioning the suspension
Keywords: Projeto de suspensão; Análise de dinâmica vertical; Dinâmica de corpos rígidos; Suspension design; Vertical dynamics analysis; Dynamics of rigid bodies; ENGENHARIAS::ENGENHARIA MECANICA::PROJETOS DE MAQUINAS